2009
DOI: 10.1007/s10164-008-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

Benthic fish exhibit more plastic crypsis than non-benthic species in a freshwater spring

Abstract: Cryptic coloration reduces the ability of predators to detect prey, but the plasticity of this defense varies. Some organisms possess static and permanent cryptic coloration, whereas in other species color changes may be induced. Depending upon the species, induced color changes may be reversible or irreversible. In this study, we examined a subtle, rapid, and reversible crypsis in which small fish exhibit muted changes in brightness to match varying substrates in clear spring water. In the laboratory, we visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
3
10
0
Order By: Relevance
“…1). A similar trend was found by Cox et al (2009) in which various 'nonbenthic' fish species of a freshwater spring exhibited reduced directional plasticity relative to the benthic species, which lives in a more spectrally heterogeneous environment. Environmental heterogeneity is assumed to select for adaptive plasticity (Buskirk, 2002;Doughty & Reznick, 2004;Schlichting, 2004).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…1). A similar trend was found by Cox et al (2009) in which various 'nonbenthic' fish species of a freshwater spring exhibited reduced directional plasticity relative to the benthic species, which lives in a more spectrally heterogeneous environment. Environmental heterogeneity is assumed to select for adaptive plasticity (Buskirk, 2002;Doughty & Reznick, 2004;Schlichting, 2004).…”
Section: Discussionsupporting
confidence: 76%
“…1). A similar trend was found by Cox et al . (2009) in which various ‘nonbenthic’ fish species of a freshwater spring exhibited reduced directional plasticity relative to the benthic species, which lives in a more spectrally heterogeneous environment.…”
Section: Discussionmentioning
confidence: 99%
“…uniformity) coloration have lower detectability on greyscale sugar maple tree trunk backgrounds. This finding corroborates those of past studies that have demonstrated that animals achieve background matching through both darkness (Vignieri et al, 2010, Kats and Vandragt, 1986, Chang et al, 2012, Cox et al, 2009) and mottled coloration (Chiao et al, 2010). However, care should be taken in generalising these results to all moth species that camouflage themselves on trees, since the experimental paradigm of positioning moths randomly on trees doesn't allow for realistic moth behaviours such as orientation (Chapter 2), body posture (Barbosa et al, 2012) and micro-patch choice (Kang et al, 2012).…”
Section: Disruptive Colorationsupporting
confidence: 85%
“…Guppy, Poecilia reticulata L In the presence of predators, populations evolve more spots and they change their size and length Endler 1980Endler , 1982Endler , 1989 Cuttlefish, Sepia officinalis (Kats and Vandragt, 1986, Feltmate and Williams, 1989, Grayson et al, 1991, Hacker and Madin, 1991, Sandoval, 1994, Johannesson and Ekendahl, 2002, Garcia and Sih, 2003, Ahnesjo and Forsman, 2006, Wilson et al, 2007, Cox et al, 2009, Vignieri et al, 2010, Clarke and Schluter, 2011, Pellissier et al, 2011, Stoner et al, 2003, Barbosa et al, 2008, Chiao et al, 2010, Bush et al, 2010, Endler, 1980, Endler, 1982, Zylinski et al, 2009, Santana et al, 2011, Kang et al, 2012, Forsman et al, 2011, Karpestam et al, 2012, Cooper and Allen, 1994, Cook et al, 2012, Hultgren and Stachowicz, 2009, Hultgren and Stachowicz, 2010 Appendix B.…”
Section: Surface Texture Matchingmentioning
confidence: 99%
“…cephalopods; Hanlon, 2007;Hanlon et al, 2009), through minutes (e.g. some poeciliid fish; Cox et al, 2009) to several weeks (e.g. several flatfish species; Ryer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%